Mortgage regulation for intermediaries - Denton, Jonathan (Butterworths, 2004)
Aims to deal with the FSA regulation as it effects the mortgage selling process. This practical guide focuses on the transactional aspects, such as when the broker can take fees; how to deal with client money; and how to manage the sales and advertising process.